Estratégias para o desenvolvimento local: diagnósticos institucionais - Murini, Lisandra Taschetto (2010)
According to deep changes, local development strategies have received special attention because the possibility of boosting stagnant regions is conjectured. The issue of research directed at evaluating the importance of IES (UNIFRA and UFSM) to promote local development strategies, especially for the region of Santa Maria (RS). The key question sets in answering the following question: what strategies and actions were developed by IES of Santa Maria that impacted and potentiated the local/regional development, in order to provide an improvement in the welfare of the community and its surroundings? The starting point of the research was an analysis of the strategies of the Institutional Development Plan (Plano de Desenvolvimento Institucional - PDI), of the IES which are involved in the study. The research highlights the importance of analyzing the PDI because it is believed that it was elaborated collectively as the guiding instrument for institutional management, for the reason that it expresses its project and vision of the future, based on institutional principles and it joint efforts to design the growth and the desired development with quality and competence. This work aims at verifying, through the existing targets in the PDI over the past five (5) years, which targets were achieved and how they contributed to promoting local development. This research is exploratory, descriptive and qualitative. Data were obtained through visits to Institutions, where the PDI of these universities were analyzed. The conclusions are that by making investments that IES have been betting on the future of the region and in the training of professionals, in general, it is in the process of continuous expansion, not only to respond to challenges, but also to seek to further integrate the region through an education with quality and competence, respecting individuals, society and promoting citizenship with responsibility and ethics.